Dermatology for the Advanced Practice Nurse. - Faye Lyons DNP, RN (Springer Publishing Company, 2014)
Unique decision trees promote accurate diagnosis and treatment of 60 common skin conditions. This is the first primary care dermatology reference written by and for nurses. It focuses on approximately 60 skin conditions that are commonly seen in primary care settings and provides unique decision trees to assist in accurate diagnosis. Organized for quick access, the book presents conditions alphabetically and includes evidence-based treatment and management strategies along with full-color photos taken during actual office visits. Dermatologic diagnostics cover skin assessment, specimen collect.